2008
DOI: 10.1007/s00535-008-2222-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of combination therapy of antiviral and immunosuppressive drugs for the treatment of severe acute exacerbation of chronic hepatitis B

Abstract: The early introduction of sufficient doses of corticosteroids and nucleoside analogs could be one option for reversing the potential deterioration of patients with clinically severe, life-threatening exacerbation of chronic hepatitis B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 25 publications
3
58
2
Order By: Relevance
“…HBV DNA is reduced rapidly following the administration of NUCs; however, the improvement to liver function is delayed by a few weeks to a few months. During this time, an excessive immune and inflammatory reaction may continue and liver cell injury may progress (17). Thus, antiviral treatment with NUCs cannot rapidly prevent disease progression and may only help to improve the short-term SS rate of acute hepatitis B-associated liver failure (25,26).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…HBV DNA is reduced rapidly following the administration of NUCs; however, the improvement to liver function is delayed by a few weeks to a few months. During this time, an excessive immune and inflammatory reaction may continue and liver cell injury may progress (17). Thus, antiviral treatment with NUCs cannot rapidly prevent disease progression and may only help to improve the short-term SS rate of acute hepatitis B-associated liver failure (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…When large numbers of degenerated hepatocytes have already been destroyed, the introduction of steroids may not be effective in improving the prognosis of liver failure (17). Fujiwara et al (17) reported that none of the eight patients studied recovered when steroids were administered >10 days after the diagnosis of SAE of chronic hepatitis B; however, 88.2% (15/17) of the patients recovered when steroids were administered within 10 days of an SAE diagnosis. The present results revealed that the time interval from the onset of symptoms to the initiation of steroid use was significantly shorter in survivors than in non-survivors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17 As an optional therapy for ACHBLF, corticosteroid treatment has received much attention. [18][19][20][21] Glucocorticoids suppresses inflammation by controlling and preventing the immune-correlated damages. The upregulation of SOCS1 by corticosteroids has been established both in vivo and in vitro, [22][23][24] which suggests that cortisol may be playing a key role in suppressing cytokine signaling and the associated inflammatory response through SOCS1.…”
mentioning
confidence: 99%